Terabaikannya Dimensi Embodied dalam Pendidikan Agama Kristen: Eksegesis 1 Korintus 6:19-20 - Guspin Trilista; Ruth Sahanaya; Albertin Ponda; Alber Lemba' Langi'; Hasni Rundung (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This research explores how the theology of embodiment in 1 Corinthians 6:19-20 can serve as a biblical foundation for integrating the embodied dimension in Christian Religious Education (CRE) pedagogy. The research background is the tendency of CRE in Indonesia to be highly cognitive-centric and neglect the embodied dimension, despite contemporary research showing the importance of sensory experience in constructing religious experience. The research objective is to conceptually explore the theological foundation and pedagogical implications of the theology of embodiment for CRE. The research method is library research with grammatical-historical exegesis analysis of 1 Corinthians 6:19-20 and conceptual synthesis with embodied cognition theory and body pedagogics. The findings show that the body has intrinsic sacred value as the temple of the Holy Spirit and the glorification of God occurs explicitly through the body. Religious knowledge is embodied, rooted in sensory-motor experience. The pedagogical implication is that CRE needs to integrate systematic embodied practices such as somatic inversion, participatory rituals, and cultivation of enactive mastery for experientially transformative learning. This research contributes theoretically by bridging biblical exegesis and embodied cognition theory, and provides practical direction for developing holistic CRE that integrates the body as an authentic and biblical medium for learning faith.